Factors Affecting the Early Completion of Ucc Postgraduate Mphil Thesis - Ansah, Newton (University of Cape Coast, 2025)
This study investigated factors that impacted the completion rates of postgraduate MPhil students at the University of Cape Coast, specifically focusing on student-related, supervisor-related, and institution-related factors. A descriptive survey with a mixed-method approach was adopted on a sample size of 53. The study used questionnaires and an interview guide for the collection of data. The questionnaire's validity was confirmed through expert review, and reliability was ensured via a pilot test, yielding high Cronbach's alpha values: student-related factors (.948), supervisor-related factors (.932), and institutionalrelated factors (.899), with an overall reliability of .793. Qualitative reliability was also ensured using Lincoln and Guba (1985) criteria. Quantitative data analysis was conducted using means and standard deviations, while qualitative data underwent thematic analysis. The study established that lack of research skills, delays in supervisor feedback, and administrative bureaucracy affect the early completion of MPhil theses. It is recommended that students prioritise commitment and engagement in their research. Also, academic institutions should ensure an improvement in supervisor support, and streamlining administrative processes. The study concluded that research skill deficits, delays in supervisor feedback, and administrative bureaucracy significantly hindered the timely completion of MPhil theses at the University of Cape Coast
xiv, 204p;, ill
Keywords: Academic writing Completion rates Graduate studies Institutional factors Postgraduate MPhil students Student-related factors Supervisor-related factors Thesis completion